Sistema Nacional de Nivelación y Admisión y su incidencia Socio Económica en los aspirantes del curso de Nivelación de la Universidad Nacional de Loja sección matutina periodo Mayo-Septiembre 2016 - Quille Soto, Erika Tatiana (2017)
Higher Education has undergone significant changes with consequences for aspirants who wish to be part of it. The present research will provide the advances and effects that have been generated through the implementation of the Public Policy of Higher Education, for this reason the present theme was selected: National Leveling and Admissions System and its Socio Economic Impact on the candidates for the Leveling Course of the National University of Loja, morning section May-September 2016. The purpose of the research is to determine the socio-economic impact of the application of the National Leveling and Admissions System in the aspiring students of the Leveling Course of the National University of Loja. It is worth mentioning the importance of this research work as such to inform the authorities responsible for implementing this public policy, what are the socio-economic effects that has generated the implementation of the System in the applicants who are part of the course Of Leveling of the National University of Loja. Finally, within the results obtained, it is concluded that the University fully complies with the development of the leveling course according to the rules of the SNNA, while the aspirants in the social field are affected because they could not choose a race for Vocation, and in the economic area the incidence is not representative because the majority of the aspirants belong to the city of Loja